2006
DOI: 10.1002/uog.3893
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester combined screening for trisomy 21 in a predominantly Chinese population

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…Unlike first-trimester combined Down syndrome screening that requires intensive training and effort in ultrasound measurement and a stringent algorithm in risk calculation to achieve a 90% detection rate with a 5% false-positive rate, [21][22][23][24] screening for fragile X carriers is relatively simple by a maternal blood test and is thus acceptable to most women. It can also be done before conception.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike first-trimester combined Down syndrome screening that requires intensive training and effort in ultrasound measurement and a stringent algorithm in risk calculation to achieve a 90% detection rate with a 5% false-positive rate, [21][22][23][24] screening for fragile X carriers is relatively simple by a maternal blood test and is thus acceptable to most women. It can also be done before conception.…”
Section: Discussionmentioning
confidence: 99%
“…86.5%) is comparable to the rates published for Caucasian (2,3,5,10,20) and Chinese populations. (21)(22)(23) This may be attributed to our centres' strict adherence to the screening guidelines established by the FMF, (19) which includes regular training and auditing of certified antenatal ultrasound sonographers. In addition, FTS attained 90.9% and 100.0% detection rates for trisomies 18 and 13, respectively, in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially since the proportion of pregnant women of advanced maternal age, defined as age 35 years and above in most countries, has increased in the past decade. It is unclear whether the widely published detection rates in the literature can be universally applied to women of all ages, especially those of advanced maternal age, as they appear to have a higher risk for fetal trisomy 21.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study on a large group of ethnic Chinese showed that the NT sonographic marker was not significantly different from that in the Caucasian populations in the first trimester [8]. A mixture model of NT thickness used for the screening of chromosome abnormalities and fetal NT followed standard distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound measurement of the fetal NT, the presence or absence of the NB, tricuspid and ductus venosus flow were performed by accredited and registered medical doctors and sonographers according to established standards of the Fetal Medicine Foundation, London UK (FMF) [7,8]. Four study groups were randomized under the FMF accreditors.…”
Section: Methodsmentioning
confidence: 99%